A dynamic study of effect of multiple parameters on interface characteristic in double-vertical explosive welding. (6th January 2020) - Sun, Zerui; Shi, Changgen; Fang, Zhonghang; Shi, Hang
Abstract: Previous studies focused on the research of single parameters on the bonding quality of explosive welded composite plates. To explore the dynamic influence of multiple parameters on the interface, a VST (velocity, stand-off gap and charge thickness) function was proposed. The three-dimensional diagram clearly and intuitively showed that the collision velocity was comprehensively affected by the explosive thickness and stand-off gap. Four different sets of parameters were chosen and the composite plates were successfully manufactured in the experiment of double vertical explosive welding (DVEW). The interface morphology, element distribution and the mechanical property were discussed respectively. The optical microscope showed that all the samples were wavy interface but the dimensions of the ripples was different. The defects, such as melting layer and island region, appeared less frequently at bonding interface when the collision velocity was lower. The grain refinement, adiabatic shear bands were found at the crest and side of wave respectively. The width of elements diffusion layer of joint increased in line with higher collision velocity. It was indicated the maximum microhardness reached 293HV at the bonding interface due to work hardening. Shear and tensile tests suggested the the mechanical property of large wave was better than that of small wavy interface. The fracture morphology showed obvious stratification and the dimple at the bonding interface was smaller in diameter and less plastic.